Primary diversification of Phaseolus in the Americas: Three centres? - Debouck, Daniel G. (1986)
The origin of 5 Phaseolus species cultivated in America (P. vulgaris, P. lunatus, P. coccineus, P. acutifolius, and P. polyanthus) is discussed within the context of a broader theory of the origin of this genus, for which 3 centers of origin may be defined: Mesoamerica, the northern and southern Andean regions. Most of their considerations have an archeological or botanical origin, but recent genetic and biochemical research works are also mentioned. (AS-CIAT)